Strategi Marketing Public Relations Gaspace dalam Membangun Brand Awareness di Era Pandemi - Mirella Putri Hadianti; Yugih Setyanto (Kiwari, 2022)
Due to the increasing price of office rentals in Jakarta every year, coworking space has become a phenomenon for workspace facilities that can be rented at affordable costs. As a result, there are many enthusiasts, increase in numbers in coworking spaces in Indonesia, especially Jakarta, even in the pandemic era. This makes the marketing public relations team required to be more creative and critical in seeing opportunities and circumstances for how to build and create brand awareness for a product. There needs to be a communication and marketing strategy that is designed to achieve this goal by utilizing existing media. The public relations theory used is mix model, namely the P.E.N.C.I.L.S. theory. Qualitative research approach with exploratory case study method. Researchers collect data by observation, in-depth interviews, and documentation. The result of the research is that public relations and marketing of Gaspace Coworking Space apply a strategy to build brand awareness initiated by Thomas L. Harris which is called the theory of the public relations mix, namely P.E.N.C.I.L.S which consists of Publicity, Event, News, Community Involvement, Inform or Image, Lobbying Negotiation, and Social Responsibility in introducing Gaspace to the wider community. Akibat harga sewa perkantoran di Jakarta semakin meningkat setiap tahunnya, coworking space hadir menjadi fenomena untuk fasilitas ruang bekerja yang dapat disewa dengan biaya terjangkau. Akibatnya banyaknya peminat maka terdapat peningkatan pada jumlah coworking space yang berada di Indonesia terlebih Jakarta meskipun di era pandemi. Hal ini membuat team marketing public relations dituntut untuk lebih kreatif dan kritis dalam melihat kesempatan dan keadaan untuk bagaimana membangun dan menciptakan brand awareness bagi suatu produk. Perlu adanya strategi komunikasi juga marketing yang dirancang untuk mencapai tujuan tersebut dengan memanfaatkan media yang ada. Teori yang digunakan adalah model bauran public relations yaitu teori P.E.N.C.I.L.S. Untuk pendekatan penelitian kualitatif dengan metode studi kasus eksploratori. Peneliti mengumpulkan data dengan observasi, wawancara mendalam, serta dokumentasi. Hasil penelitian adalah Public relations dan marketing Gaspace Coworking Space menerapkan strategi untuk membangun brand awareness yang diprakarsai oleh Thomas L. Harris yang disebut teori bauran public relations yaitu P.E.N.C.I.L.S yang terdiri dari Publicity, Event, News, Community Involvement, Inform or Image, Lobbying Negotiation, dan Social Responsibility dalam memperkenalkan Gaspace kepada masyarakat luas.